PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI SISTEM REGULASI PADA MANUSIA DENGAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) PADA SMA KARTIKA WIRABUANA MAKASSAR - Hakim, Abd (Jurnal Biotek, 2013)
This research aimed to produce valid, practical and effective learning packages on the topic of human regulatory system by applying cooperative model of NumberedÂ Head Together (NHT) type at SMA Kartika Wirabuana I Makassar.The subjects of this study were 30 grade XI students of IPA.1 at SMA Kartika Wirabuana I Makassar second semester 2010/2011 academic year. The data of this study were obtained from packages validation results, research instruments that collected by experts, evaluators, observers and questionnaire responses from students which were analysed quantitatively.The developed learning packages were learning plan (RPP), studentâs book (BS) and studentâs worksheet (LKS). This research found that the validity value of the learning plan (RPP), the studentâs book (BS) and the studentâs worksheet (LKS) on each evaluated aspects were categorised as âvalidâ (3.5 â¤ X â¤ 4.5) and âextremely validâ (4.5 â¤ X â¤ 5). These results indicated that the cooperative learning model of numberedÂ head together (NHT) type on the topic of human regulatory system have been valid. The practical of the packages was also categorised in âcompletely implementedâ (1.5 â¤ M â¤ 2.0) with 2.0 ideal value and 86.08% desagreement percentage. The effectiveness was evaluated from: (1) positive responses of the students to the learning model, studentâs book and studentâs worksheet, (2) All of the studentsâ activities were completed within ideal time intervals, (3) Teacherâs ability in managing the learning process was categorised in âhighâ (2.5 â¤ KG â¤ 3.5) and âextremely highâ (3.5 â¤ KG â¤ 4), and (4) the results of the studentsâ classical learning test which was 85% with 12.58 standard deviation ( X Â± SD ).